2019
DOI: 10.3390/w12010041
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Data Management and Numerical Modelling: Demonstrating the Application of the QGIS-Integrated FREEWAT Platform at 13 Case Studies for Tackling Groundwater Resource Management

Abstract: Because of the spatial nature of groundwater-related data and their time component, effective groundwater management requires the application of methods pertaining to the Information and Communication Technologies sector, such as spatial data management and distributed numerical modelling. The objective of this paper is to demonstrate the effectiveness of the QGIS-integrated FREEWAT platform and an approach combining spatial data management and numerical models to target groundwater management issues. FREEWAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Challenges exist in understanding system dynamics and the flow patterns, analyzing the groundwater responses to stresses in the system, and assessing the sustainable groundwater yield. In short, groundwater modeling is an area of continued research, as identified by several publications [4][5][6][7][8][9]. The groundwater flow is governed by the well-known Boussinesq equation.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges exist in understanding system dynamics and the flow patterns, analyzing the groundwater responses to stresses in the system, and assessing the sustainable groundwater yield. In short, groundwater modeling is an area of continued research, as identified by several publications [4][5][6][7][8][9]. The groundwater flow is governed by the well-known Boussinesq equation.…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated tools for pre-processing of field data [53,54] and for post-processing of models' results are integrated as well. FREEWAT was applied to date to a variety of case studies [55]. The present work may be considered as a continuation of the research activities performed to better describe agricultural water use in hydrological modelling.…”
Section: Overview Of the Freewat Platformmentioning
confidence: 99%
“…A new ArcGIS tool for groundwater flow simulation and visualization of results was also implemented by [19]. Other authors (De Filippis et al [31]) applied a previously developed GIS-based tool (AkvaGIS), in addition to a groundwater flow model, to study the impacts of pumping on seawater intrusion in coastal aquifers in Malta and Italy. is tool was used in other studies (Perdikaki et al [32]) to analyze hydrochemical parameters in a coastal aquifer that presented seawater intrusion problems.…”
Section: Related Workmentioning
confidence: 99%